SUSTAINING CLIMATE CHANGE MITIGATION—POLICY, TECHNOLOGY, AND SOCIETY - Andreas Rechkemmer (Geography, Environment, Sustainability, 2010)
In a world that is becoming more and more exposed and vulnerable to the effects of global climate change, combining integrated risk assessment tools with effective strategies for both mitigation and adaptation is a key prerogative for policy-making. With the focus of both researchers and decision-makers gradually shifting from observing and assessing the bio-physical aspects of climate change to a more human and society centered understanding of the nature of the problem, the social, behavioral, economic and technological aspects have entered center stage of the public discourse. Responses to the climate change challenge have to establish an optimal interplay between mitigation, adaptation and socio-economic instruments. Yet, given the band-width and scale of the climate problematique and its projected impacts, very ambitious mitigation measures have to be undertaken without delays, a fact that is particularly true for emerging economies with their very rapid and unprecedented growth rates, both in GDP and GHG emissions terms. The challenge for the next years is to harmonize poverty eradication and attaining the Millenium Development Goals through stable economic growth with mitigating the effects of climate change. Therefore, “inclusive green growth” has become the motto of the day. But how can this goal be achieved? Obviously, quite fundamental changes have to be introduced that affect both the production and the consumption sectors and allow for real innovation in technologies and energy, in urban mobility, infrastructure and transportation grids. This paper illustrates the deep social and societal nature of climate change response strategies, especially in the area of mitigation, and shows that transitions to green and low-carbon economies will have to embed policies, incentive schemes and economic instruments in a larger societal context of social learning and behavioral change.